The role of performance analysts within the coaching process: Performance Analysts Survey 'The role of performance analysts in elite football club settings.' - Wright, C.; Atkins, S.; Jones, B.; Todd, J. (International Journal of Performance Analysis in Sport, 2013)
The aim of this study was to identify the role which performance analysts play within elite football clubs and identify how these roles differ within professional and academy settings. This study addressed the dearth of research regarding the role of match analysts, in relation to the provision of feedback via match and notational analysis techniques and systems. An exploratory study was conducted using an online questionnaire, formed using knowledge from current match analysts working in elite football, academic practitioners within the areas of performance analysis and from current literature. The questionnaire was completed by 48 match analyst practitioners working within elite football clubs. 32 of the analysts were predominantly working in a professional team setting, while 16 were predominantly working in an academy setting. When comparisons were made between the two groups of analysts a number of significant differences (P<0.05) were identified in relation to the provision of pre match feedback, post-match feedback and the value the analysts gave to certain performance analysis approaches. 4 of these factors related to pre match feedback, 1 factor related to post match feedback and the remaining 9 factors related to value associated with performance analysis approaches. Further insight has been provided into the importance of the role analysts play in enhancing the observation, analysis and feedback strategies which elite level football teams utilise.